DEN PEDAGOGISKE FILOSOFIENS OPPDRAG - Strand, Torill (Studier i Pædagogisk Filosofi, 2012)
Today, philosophy of education comes forward as diverse, many-faceted and numerous engagements with issues and problems concerning both the fields of philosophy and education. But what is the vital mission of contemporary philosophers of education, and how is this mission justified? Through a tentative reading of Alain Badiou’s ethic and philosophical manifestos, I here hope to throw some lights on these questions. To do so, I clarify Badiou’s epistemic and ontological positions and discuss the relevance of his “ethic of truths” and “democratic materialism”. To what degree may Badiou inform the potential topicality and relevance of a philosophy of education of and for the present?